2013
DOI: 10.1021/jp400694k
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemistry, Surface Plasmon Resonance, and Quartz Crystal Microbalance: An Associative Study on Cytochrome c Adsorption on Pyridine Tail-Group Monolayers on Gold

Abstract: Quartz crystal microbalance (QCM), surface plasmon resonance (SPR), and electrochemistry techniques were used to study the electron-transfer (ET) reaction of cytochrome c (Cyt c) on gold surfaces modified with thionicotinamide, thioisonicotinamide, 4-mercaptopyridine, 5-(4-pyridyl)-1,3,4-oxadiazole-2-thiol, 5-phenyl-1,3,4-oxadiazole-2-thiol, 4,4'-bipyridine, and 4,4'-dithiopyridine. The electrochemical results showed that the ET process is complex, being chiefly diffusional with steps depending on the orientat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 62 publications
3
10
0
Order By: Relevance
“…On the basis of the knowledge that a hydrophilic pocket composed of positively charged amino acid residues surrounds the T1 Cu, many other studies also reported that carboxylate groups on the surface of electrodes allow fast electron transfer for adsorbed Mv BOD. , Although this observation is commonly accepted to be related to a suitable orientation of the enzyme on the surface, the proof of such an orientation and the way in which the conformation and amount of adsorbed proteins evolved in relation to the catalytic activity have only seldom been reported. , Coupled methods were used to get further insights into the relation between the enzymatic activity and the immobilized enzyme amount and conformation. , Quartz crystal microbalance measurements coupled with electrochemistry (e-QCM) was especially carried out to study Mv BOD activity on negatively charged interfaces. , It was shown that electroactivity loss did not correlate with enzyme leaching but with structural rearrangements. , Surface plasmon resonance (SPR) is another method that can be coupled with electrochemistry in order to obtain information about adsorbed species at the electrochemical interface . Any perturbation at the surface induces change in the refractive index of the adsorbed layer that is monitored through the modification in the resonant angle of light as a result of light adsorption by surface plasmons. , Electrochemistry coupled with SPR (e-SPR) has been used in the past to study electron transfer on cytochrome c as a function of SAM chemistry on a gold electrode, redox state induced immobilization of ferrocene-modified proteins, effects of nanostructuration of materials on the activity per bound glucose oxidase molecule, and assemblies of various nanomaterials and enzymes for biosensor applications …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the knowledge that a hydrophilic pocket composed of positively charged amino acid residues surrounds the T1 Cu, many other studies also reported that carboxylate groups on the surface of electrodes allow fast electron transfer for adsorbed Mv BOD. , Although this observation is commonly accepted to be related to a suitable orientation of the enzyme on the surface, the proof of such an orientation and the way in which the conformation and amount of adsorbed proteins evolved in relation to the catalytic activity have only seldom been reported. , Coupled methods were used to get further insights into the relation between the enzymatic activity and the immobilized enzyme amount and conformation. , Quartz crystal microbalance measurements coupled with electrochemistry (e-QCM) was especially carried out to study Mv BOD activity on negatively charged interfaces. , It was shown that electroactivity loss did not correlate with enzyme leaching but with structural rearrangements. , Surface plasmon resonance (SPR) is another method that can be coupled with electrochemistry in order to obtain information about adsorbed species at the electrochemical interface . Any perturbation at the surface induces change in the refractive index of the adsorbed layer that is monitored through the modification in the resonant angle of light as a result of light adsorption by surface plasmons. , Electrochemistry coupled with SPR (e-SPR) has been used in the past to study electron transfer on cytochrome c as a function of SAM chemistry on a gold electrode, redox state induced immobilization of ferrocene-modified proteins, effects of nanostructuration of materials on the activity per bound glucose oxidase molecule, and assemblies of various nanomaterials and enzymes for biosensor applications …”
Section: Introductionmentioning
confidence: 99%
“…35 Any perturbation at the surface induces change in the refractive index of the adsorbed layer that is monitored through the modification in the resonant angle of light as a result of light adsorption by surface plasmons. 36,37 Electrochemistry coupled with SPR (e-SPR) has been used in the past to study electron transfer on cytochrome c as a function of SAM chemistry on a gold electrode, 38 redox state induced immobilization of ferrocene-modified proteins, 39 effects of nanostructuration of materials on the activity per bound glucose oxidase molecule, 40 and assemblies of various nanomaterials and enzymes for biosensor applications. 41 In this work, we perform e-SPR to study for the first time the relationship between the loading and activity of Mv BOD adsorbed on two different SAMs.…”
Section: Introductionmentioning
confidence: 99%
“…To understand the correlation between molecular dynamic behavior and the electrochemical response of proteins adsorbed on the electrode, numerous studies have used spectro-electrochemical techniques that combine electrochemical measurements and various spectroscopy techniques, such as surface-enhanced resonance Raman (SERRS) [ 1 3 ] and surface-enhanced infrared absorption (SEIRA) [ 4 6 ]. Electrochemical quartz crystal microbalance (EQCM) and surface plasmon resonance (SPR) measurements also have been used to study dynamic molecular adsorption processes [ 7 9 ]. These techniques provide excellent opportunities to study redox protein mechanisms and provide overall information concerning the interface between proteins and an electrode; however, the local structure is not obtained, due to a lack of spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that cyt c electrostatically immobilizes on SAMs of carboxylic acid-terminated alkanethiols via lysine residues surrounding the cyt c heme crevice and exhibits a reversible voltammetric response [ 22 27 ]. Numerous studies on direct electrochemistry of cyt c adsorbed on a SAM-modified [ 25 ] electrode have employed various surface analysis techniques [ 5 , 9 , 11 , 28 33 ]. Until now, however, cyt c molecules adsorbed on electrodes have not been directly observed through real-time imaging using microscopy techniques.…”
Section: Introductionmentioning
confidence: 99%
“…QCMs have been proven to be reliable in the field of electrochemistry (Paulo Tde et al, 2013; Sun et al, 2013a, 2013b), in petroleum characterization (Pejcic et al, 2011; Ueyama et al, 2002), in environmental chemistry (Nicolini et al, 2012), material science (Pei et al, 2010) and more interestingly in the development of biosensors (Bouchet-Spinelli et al, 2013; Eom et al, 2013; Guntupalli et al, 2013; Wangchareansak et al, 2013) which are valuable for disease diagnosis. QCMs also found a great interest in the monitoring of the affinity constants defining a given substrate-ligand interaction (Lebed et al, 2006; Li et al, 2013; Mori et al, 2009; Tan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%